Empowering Junior High School Students' Thinking Skills Through the Application of Problem-Based Learning Models - Gamar B. N. Shamdas; Lestari Alibasyah; Isnainar; Zulaikhah Dwi Jayanti (Postgraduate, University of Mataram, 2025)
The reason for this review is to portray imaginative reasoning abilities and science-critical abilities to think in middle school understudies by using issue-based learning models. The study was directed at class VIII students at one of Palu City's junior high schools. The population of class VIII consists of five classes totaling 160 students. Purposive sampling was used to select two classes as samples. Data on problem-solving and creative thinking abilities were obtained through essay tests. The instruments used were teaching modules, LKPD, and tests. Information investigation utilized an autonomous t-test with the assistance of SPSS variant 25.0. The findings revealed that the creative thinking skills in conventional classes were significantly lower than problem-based learning classes t(62)=13.56, p<0.001, and problem-solving skills in conventional classes were considerably lower than problem-based learning classes t(62)=14.63, p<0.001. Thus, this study concludes that the creative thinking skills and problem-solving abilities of Class VIII SMP students in science subjects can be empowered by implementing a problem-based learning model.